How are Irish Primary Teachers using Social Media to Influence their Visual Arts Teaching Practice? - Lawrence, Amy (Marino Institute of Education, 2020)
The first study of its kind in Ireland, this study explored what types of social media platforms were used by Irish primary school teachers when planning for and teaching visual arts. A mixed-methods research approach was used, with eight primary school teachers completing questionnaires and participating in semi-structured interviews. The participants all held a positive attitude towards teaching art but lacked confidence in creating their own art lesson ideas. Seven of the participants referred to their frequent use of social media platforms such as Pinterest or Instagram for art lesson ideas; these participants used the platforms to search for and store art lesson ideas for their future use. The nature of the curated content found on social media had several implications for teachers’ art lesson planning. Participants reported teaching art lessons using images directly sourced from social media; participants felt that the content posted by teachers on social media was an unrealistic portrayal of the typical classroom, yet felt pressured to emulate the lessons and displays posted by other teachers on their social media pages. The issue of teacher criticality of online content was also explored. While the participants of this study were cognisant of the importance of the artistic process, art lessons found on social media were assessed to some extent by participants in terms of relevance to the curriculum, but there was no evidence of these lesson ideas being critiqued for accuracy or reliability. This small-scale study concluded that primary teachers’ use of social media to plan and teach art lessons should be explored further. Though this study was carried out in Ireland, its findings are applicable to other jurisdictions. From a quality visual arts education perspective, it is necessary to further assess how art lessons originating on social media are being taught in classrooms and what the implications are for learners’ visual arts experiences.